How Do We Improve Public Expenditure in Agriculture? - World Bank (World Bank, 2012)
This paper synthesizes lessons learned from the Department for International Development-World Bank (DFID-WB) partnership, to provide guidance on ways to improve the allocation and efficiency of public spending for agricultural growth and poverty reduction. It includes lessons on how to improve data quality, the composition and impact of spending, budget execution, and the integration of off-budget expenditures. The paper synthesizes recurring lessons that have emerged from the commissioned work, to highlight key challenges that still remain to improve the efficiency of public expenditure planning and implementation in the agriculture sector, as well as offering options for improvement. The paper is accompanied by a separate document, the Agricultural Public Expenditure Reviews (AgPER) toolkit, which is a practical guide for practitioners tasked with carrying out AgPERs in the future. The paper is structured around the Budget Cycle Framework (BCF), to facilitate the identification of entry points to improve expenditure outcomes.